Dinâmica, produção e valor nutritivo de pastagens tendo como base o capim-elefante consorciado com amendoim forrageiro - Antunes, Monique Évelyn de Lima (2023)
Elephant grass stands out for its high potential for forage production in different regions of the country. In most properties, elephant grass is cultivated intensively with high doses of mineral fertilizers, mainly nitrogen fertilizers, which makes production expensive and less sustainable. In this context, intercropping elephant grass with forage legumes can make the system more efficient and with less environmental impact. Thus, the objective of this research was to evaluate forage systems, regarding the dynamics, production and nutritional value of the pastures, and stocking rate, based on elephant grass intercropped with forage peanut under grazing conditions with lactating cows over the course of an agricultural year. The treatments consisted of two forage systems (with x without legumes). The standardization criterion for forage systems was the level of nitrogen fertilization (120 kg/ha/year of N). Pre- and postgrazing forage samples were taken to determine the botanical composition of pastures and morphological composition of elephant grass, and to estimate forage production. Forage samples, simulating grazing, were collected manually at the beginning and at the end of each grazing to evaluate the nutritive value. The presence of forage peanuts affected the botanical composition of the pasture, with a reduction in spontaneously growing species and dead material, as well as in the morphology of elephant grass, with a higher proportion of leaf blades, and less stem plus sheath and senescent material. In the forage system with legume, there was an increase in forage production and stocking rate and better nutritional value of forage.